Agile Blueprints: Navigating Project Management toward Sustainable Success: A Comprehensive Literature Synthesis and Managerial Compass - AlOwais, AbdelAziz (International Review of Management and Marketing, 2024)
This paper is constructed to study the sustainable practices that project managers follow and their contribution to sustainability. This study divides the sustainability section into three pillars (Economic, Environmental, and social). Sustainability is still an emerging concept with multiple interpretations globally. This paper also discusses several scenarios comparing and contrasting those practices to draft suitable recommendations. Moreover, this paper studies the link between sustainability and agility. As this paper is conceptual in nature, only scholarly articles ranging from Q1 to Q4 can be accepted to report findings and critique academically. Primary methods will not be utilized in this paper. As per each contribution the findings are also categorized into three pillars of sustainability. The findings are linked codes to each sustainable practice as cited earlier including agility being an independent variable. The research recommends testing the hypothesis and propositions in case the study develops further. The findings from past literature will be utilized to create critical success factors and recommended models. As this paper is conceptual research, the paper lacks empirical data, and it uses inductive philosophy to create themes and findings.